APLIKASI PUPUK KANDANG SAPI DAN BERBAGAI JENIS MIKROORGANISME LOKAL (MOL) SERTA PENGARUHNYA TERHADAP PERTUMBUHAN KEDELAI (Glycine max Merill L.) - Saartje ., Sompotan; D. M. F. Sumampow; Antje G. Tulungen; Maria ., Montolalu; Rinny ., Mamarimbing; Stella M. Th. Tulung (EUGENIA, 2020)
The purpose of this research was to obtain the interaction between the dose of cow manure and the type of local microorganism (MOL) in increasing soybean growth, to obtain the dose of cow manure and the dose of MOL that gave the best growth of soybean plants. The two-factor factorial study used a completely randomized design. The treatment consisted of, Factor I (A) = Dosage of Cow Manure. A1 = 10 tons/ha, A2 = 20 tons/ha, A3 = 30 tons/ha. Factor II (B) = Type of Local Microorganisms (MOL). Bo = No MOL; B1 = MOL Banana hump (5 liters/ha); B2 = MOL Papaya (5 liters/ha), B3 = MOL Rice (5 liters/ha). Each treatment was repeated three times to obtain 36 experimental pots. The variables observed were: plant height and number of leaves as primary data and N, P, K content in each MOL as secondary data). Primary data were analyzed using analysis of variance and if there was a difference, it was continued with the Least Significant Difference Test (BNT) at the 5% test level. The results showed that the interaction between cow manure and various types of MOL significantly affected plant height and number of soybean leaves. 20 tons of cow manure on MOL banana weevil increased the growth of plant height and number of soybean leaves.